Dinamika Perubahan Tutupan Lahan dan Emisi Karbon dari Deforestasi dan Degradasi Hutan di Kabupaten Kutai Timur Tahun 2019 - 2024 - Fauzan, Muhammad Rafii Nur; Suhardiman, Ali; Naufalianto, Ikhsan Fiqra; Syarifudin, Achmad; Nugroho, Andi; Saud, Oshlifin Ruchmana (Universitas Pattimura, 2025)
This study aims to analyze land cover changes and estimate carbon emissions resulting from deforestation and forest degradation in Kutai Timur Regency during the period of 2019–2024. The analysis was conducted using land cover vector data from the Ministry of Environment and Forestry, which was analyzed with the pairwise comparison method and Geographic Information System (GIS). Carbon emissions were calculated based on Tier 2 IPCC with emission factors for each land cover class.The results of the study show that deforestation is the main contributor to carbon emissions, with the highest increase in emissions during 2023–2024, reaching 9,702,628 tons CO₂e. The decrease in emissions during 2020–2022 aligns with the implementation of the moratorium policy, but an increasing trend in emissions was observed again in 2022–2024, indicating that pressure on forest land remains high. Natural regeneration of secondary forests occurred, but its contribution was not sufficient to offset the loss from deforestation. Spatial patterns show that the largest forest conversion took place in agricultural areas, mining, open land, and scrublands. These findings emphasize the importance of consistent jurisdiction-based forest management policies to achieve the FOLU Net Sink 2030 target and support climate change mitigation.